The Effect of Profitability, Corporate Governance, Inventory Intensity on Tax Avoidance (in Mining Companies listed on the Indonesia Stock Exchange for the period 2017-2021) - Natalina (International Journal of Science and Society, 2023)
The larger the profit, the greater the amount of income tax that will need to be payed. Meanwhile, taxes are sometimes viewed as a "burden" for businesses, thus some attempt to minimize their taxes. The goal of this research is to look into the effects of profitability, corporate governance, and inventory intensity on tax avoidance in mining companies. In this investigation, the quantitative technique was used. This study utilizes information from the financial statements of mining companies listed on the IDX in 2017-2021. The use of samples selected was 50 out of a total of 125 companies. Multiple liner regional analysis performs analysis procedures and hypothesis testing. Eviews-12 is used to process data. Profitability has an effect on tax avoidance, according to the test results. Tax avoidance is unaffected by independent commissioners, audit committees, or inventory intensity.